Eggerthia catenaformis bacteremia in a patient with an odontogenic abscess. (June 2019) - Foronda, Carla; Calatrava, Elizabeth; Casanovas, Isabel; Martín-Hita, Lina; Navarro-Marí, José María; Cobo, Fernando
Abstract: Eggerthia catenaformis is a Gram-positive anaerobic rod, which has been rarely reported in human diseases. We report the second case of bacteremia due to this microorganism in an elderly patient. A 73-year-old man, without underlying diseases presented with fever, odynophagia and swelling of the cervical lymph node for several days. Culture of drained cervical fluid resulted in the isolation of Raoultella ornithinolytica and Streptococcus anginosus . Anaerobic blood cultures yielded a rare anaerobic microorganism, identified as Eggerthia catenaformis . No resistance to tested antimicrobials was documented. Treatment with drainage and several antibiotic regimens was established, and the general condition of the patient improved, at two months of follow-up. Highlights: Eggerthia catenaformis is rarely associated with human infections. E. catenaformis causes infection in patients with dental alterations. Mass spectrometry is a useful tool in the diagnosis of this species. Our strain was susceptible to all antibiotics tested.